ANALISIS KESALAHAN KATA KERJA BANTU â€œYINGGAIâ€ , â€œDEIâ€, â€œBIXUâ€ PADA MAHASISWA PRODI PENDIDIKAN BAHASA MANDARIN - Nurhikmah, Nurhikmah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstrak In Mandarin there are many auxiliary verbs of similar use, such as "yinggai", "dei" and "bixu". This is why the students often make mistakes in using it, therefore the authors do the research about mistakes in the use of auxiliary verbs "yinggai", "dei" and "bixu" in the student class of 2015 majoring in Chinese Language Education Faculty of Teacher Training and Education University of Tanjungpura. The authors studied in the student class of 2015 majoring in Chinese Language education Faculty of Teacher Training and Education University of Tanjungpura in using auxiliary verbs "yinggai", "dei" and "bixu". Based on the data obtained, the authors analyzed the student error in using the three auxiliary verbs. The authors conclude that the percentage of errors in the use of "yinggai", "dei" and "bixu" in the student class of 2015 majoring in Chinese Language Education Faculty of Teacher Training and Education University of Tanjungpura are 28.1%, 33.0% and 27.6%, and the types of errors that are often encountered are errors of word selection and word-making errors. While the cause of the error is the influence of foreign language rules learned.Keywords: Auxiliary Verb Yinggai, Dei, Bixu Error Analysis